Understanding the role of bitter taste perception in coffee, tea and alcohol consumption through Mendelian randomization. Issue 1 (December 2018) - Ong, Jue-Sheng; Hwang, Daniel; Zhong, Victor; An, Jiyuan; Gharahkhani, Puya; Breslin, Paul; Wright, Margaret; Lawlor, Deborah; Whitfield, John; MacGregor, Stuart; Martin, Nicholas; Cornelis, Marilyn
Abstract Consumption of coffee, tea and alcohol might be shaped by individual differences in bitter taste perception but inconsistent observational findings provide little insight regarding causality. We conducted Mendelian randomization analyses using genetic variants associated with the perception of bitter substances (rs1726866 for propylthiouracil [PROP], rs10772420 for quinine and rs2597979 for caffeine) to evaluate the intake of coffee, tea and alcohol among up to 438, 870 UK Biobank participants. A standard deviation (SD) higher in genetically predicted bitterness of caffeine was associated with increased coffee intake (0.146 [95%CI: 0.103, 0.189] cups/day), whereas a SD higher in those of PROP and quinine was associated with decreased coffee intake (−0.021 [−0.031, −0.011] and −0.081 [−0.108, −0.054] cups/day respectively). Higher caffeine perception was also associated with increased risk of being a heavy (>4 cups/day) coffee drinker (OR 1.207 [1.126, 1.294]). Opposite pattern of associations was observed for tea possibly due to the inverse relationship between both beverages. Alcohol intake was only negatively associated with PROP perception (−0.141 [−1.88, −0.94] times/month per SD increase in PROP bitterness). Our results reveal that bitter perception is causally associated with intake of coffee, tea and alcohol, suggesting a role of bitter taste in the development of bitter beverage consumption.